Komunikasi Kesehatan Berbasis Virtual Pada Komunitas Ketofastosis Dalam Membangun Pemahaman Kesehatan - Novrian, Novrian; Suharjuddin, Suharjuddin; Rina Sovianti, Rina Sovianti (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
Community empowerment as a government partner in dealing with health issues is expected to improve public health in society. Today many communities are formed in an effort to address health issues. One of the communities that is currently in the spotlight of the general public is the ketofastosis Indonesia community (KFI). KFI was initiated and introduced to the public by Nur Agus Prasetyo. The community was formed in 2016. The large role of the community present in this online media also gives its own meaning to the members who are members of it. The formation of meanings between one individual and another is certainly different because each human being has a unique character. The problem of this study is what does warrior means for the perpetrators of Ketofastosis? The purpose of this study is to know the meaning of warrior for the perpetrators of Ketofastosis. The study used virtual ethnographic research methods and used the research subjects of two groups on social media whats app and instagram. The results of this study concluded the term warrior has two meanings for KFLS actors, namely beginner warrior and warrior mentor. Beginner warriors are KFLS actors who tend to ask and confirm whether the activities or food they consume are in accordance with procedures or not. This beginner warrior behavior in interacting shows that communication is a process by which individuals coordinate their behavior with a shared interpretive scheme. Warrior mentors are motivating people, forming a comfortable atmosphere and environment for budding warriors who still have doubts and fears in undergoing KFLS.